Importance Assessment of Structural Members Based on Elastic-Plastic Strain Energy - Yongjun Lin; Xianzhao Zhang; Wenqiang Xu; Meng Zhou (Advances in Materials Science and Engineering)
Based on the elastic analysis, the existing methods of the importance assessment of structural members can only reflect the structural elastic behavior. To understand the plasticity and stiffness degradation of the structure, the present study proposes a member importance assessment method which takes the structural elastic-plastic strain energy or the generalized elastic-plastic strain energy as the performance parameter. First, the existing methods of member importance assessment are explained. Second, by pushover analysis, structural elastic-plastic strain energy is calculated in accordance with the story force-displacement curve, and structural generalized elastic-plastic strain energy is calculated according to the base shear-top displacement curve. Third, the importance of structural members is measured with its effect on the elastic-plastic strain energy or generalized elastic-plastic strain energy of the structure. Given the difference between structural performance parameters, the coefficient of member importance is defined. Finally, the importance of the masonry structure wall is quantitatively assessed using the elastic-plastic strain energy method, the generalized elastic-plastic strain energy method, the generalized stiffness method, and the ultimate bearing capacity method. Besides, the effect of the seismic fortification intensity and the number of structural stories on the wall importance assessment results is analyzed. According to the results, the elastic-plastic strain energy method and the generalized elastic-plastic strain energy method can both reveal the mechanical performance of elastic-plastic state of the structure under severe earthquake. Furthermore, the greater the seismic fortification intensity is, the more important the wall will be on the bottom floor, the more the total number of structural stories will be, and the more important the opening wall and its adjacent wall will be.